De porta adentro à porta afora: trabalho escravo nas freguesias do Espírito Santo (1850-1871) - Jesus, Aloiza Delurde Reali de (2009)
This dissertation, From door to door within: slave labor in the parishes of the Espírito Santo (1850-1871),has the objective of presenting the main aspects of the work performed by slaves in the parish of the Espírito Santo, in particularly Vitória, principal of the province, and villages neighbors in the period 1850 to 1871. The main groups of sources were analyzed for District Criminal Court of Vitória (Judicial Division of the Province) and the regular newspaper of Victoria, Victoria and the official The Espirito Santense. Consideration was also the 1st Book of the classification of slaves to be freed of the City of Vitória and the letters sent by authorities to City of Vitória. Through the study of these documents, there was, first, that the slaves were local, mostly, small and medium, formed by a balanced number of men and women and a significant number of children. These findings led to the fundamental importance of family arrangement in the formation and expansion of slaves located in Vitória and neighborhoods. This configuration of the captive stocks has also found that slave labor had developed in this region with the intense participation of women and children in all types of occupations. The daily work of these captives showed even they developed almost indiscriminately tasks typically rural and urban areas, pointing to a lack of differentiation or specialization among captive or exclusive in their employment arrangements. Finally, we notice with this dissertation, that the method of work of the slave never prevented the strong sociability among the captives and other social strata, marked by great mobility and spatial relations that often exceeded the limits of captivity.